A COGNITIVE THEORY DRIVEN NEW ORIENTATION OF INDONESIAN LESSONS - Nowinska, Edyta (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
The main focus of this design research was on studentsÃ¢â‚¬â„¢ mathematical thinking and skills andÃ‚Â on their understanding of mathematical concepts and methods. The mathematical content ourÃ‚Â project starts with is the introduction of integers. For this content new learning environmentsÃ‚Â have been developed, implemented and evaluated. An important question for the design ofÃ‚Â teaching and learning activities is how to establish appropriate models of mathematicalÃ‚Â concepts and methods for students and how they operate in studentsÃ¢â‚¬â„¢ minds. In the lecture theÃ‚Â use of those methodological concepts and theories in our approach will be explained andÃ‚Â justified. The results indicate that the means and methods used in our project have a positiveÃ‚Â influence on the quality of teaching and learning processes in the class and on studentsÃ¢â‚¬â„¢Ã‚Â mathematical thinking and skills.Keywords: Cognitive Theory, Indonesian Lessons, Mathematical ConceptÃ‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1501.170-190